Exclusive Breastfeeding Among Working Mothers: The Impact of Self-Efficacy and Family Support - Zalfadila Fahira; Asti Dewi Rahayu Fitrianingsih; Fajria Saliha Puspita Prameswari; Widya Astuti (Universitas Malahayati, 2026)
ABSTRACT This study examined the impact of maternal self-efficacy and family support on exclusive breastfeeding among working mothers in DKI Jakarta, the region with the lowest exclusive breastfeeding rates on Java despite gradual increases from 65.63% in 2021 to 76.39% in 2023, which remain below the national target of 80%. This study aims to determine the relationship between maternal self-efficacy, family support, and exclusive breastfeeding among working mothers in Jakarta. A quantitative cross-sectional design was used from August 2024 to August 2025 across five administrative regions, involving 77 purposively selected working mothers. Data collection utilized structured interviews with validated and reliable questionnaires. Statistical analyses included univariate analysis, simple logistic regression, and multiple logistic regression. The findings revealed a significant relationship between maternal self-efficacy and exclusive breastfeeding (OR = 0.243; 95% CI = 0.09–0.71; p = 0.006), while family support showed no significant association (OR = 0.418; 95% CI = 0.127–1.285; p = 0.094). These results highlight the key role of maternal confidence in promoting exclusive breastfeeding among working mothers. Interventions and educational programs to enhance maternal self-efficacy are, therefore, recommended to increase breastfeeding rates. However, the cross-sectional design, small sample size, and purposive sampling limit causal interpretation and generalizability. Future longitudinal or experimental studies are encouraged to confirm results and identify additional influencing factors. Keywords: Exclusive Breastfeeding, Working Mothers, Self-Efficacy, Family Support, Cross-Sectional Study, Jakarta.